TINGKAT PENERAPAN TEKNOLOGI BUDIDAYA SAYURAN ORGANIK DI KELURAHAN KARANGREJO KECAMATAN METRO UTARA KOTA METRO - Arum Purnawati; Sumaryo Gitosaputro; Begem Viantimala (Lampung University, 2015)
The aim of this research is to know the application level of organic vegetables cultivation technology in Karangrejo Village North Metro sub district, Metro City. This research was conducted May until June 2014 in Karangrejo Village North Metro sub district, Metro City. The research method used case study to got samples with Arikunto’s formula, by working 48 respondents. The data analysis was done descriptively. The results showed that: The application level of organic vegetables from cultivation technology in Karangrejo Village in the middle category with an average level applicability of 75 percents. The application level of technology have been applied well, there are activities on planting, watering, and post harvesting. The level of implementation needs to be improved were seeds/seedlings and harvesting. Key words: application, technology, organic vegetables